Industrial training report: Melaka International College of Science and Technology (MiCoST) Library / Ezuhijjahh Norikmah Ezal' Ain - Ezal' Ain, Ezuhijjahh Norikmah (Universiti Teknologi MARA, Negeri Sembilan, 2022)
Students that pursuing a Degree in Information Management (Library Management) at University Technology MARA (UiTM) must complete industrial training as a part of their programme. This industrial training programme is taken part of 22 weeks with 12 credit hours programme for students which taken from September 1, 2021, to January 31, 2022. Students are given an option in choosing the place for their industrial training, whether a governments or private institutions. This programme was being created to help all graduates develop the skills they need also allows them to study the worked environment to increase their marketability and careers. Students can utilise their learning theory in institutions of industrial training and gain variety of new skills during practical. Other than that, this programme also to help students develop their own personalities, improves soft and technical skills, enhances discipline in works ethics and regulations, and provide exposure to the workplace. Furthermore, industrial training can help students to boost their self-esteem and encourage them to pursue professions in their chosen fields in the future.